Concluding remarks (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
The concluding remarks examines the role of objects as commodities in the late Middle Ages through written and material sources, highlighting shifts in their social and economic perception. Historical documents such as customs records, account books, and inventories demonstrate the growing importance attributed to objects, both as status symbols and consumer goods. Following the 14th-century plague, there was a notable increase in consumption and the spread of luxury items, reflecting a more hedonistic mentality. Archaeological analysis complements historical research by linking artifacts to specific social contexts and uncovering often hidden economic and cultural dynamics. The comparative approach between material and written sources provides a multifaceted understanding of late medieval societies, revealing the complex social and economic relationships tied to objects, from production to consumption. The volume underscores the need for an integrated and critical interpretation of sources to fully grasp the role of objects in the material culture and society of the period.
Keywords: Commodities; Late Middle Ages; Material Culture; Social Contexts; Consumption